CaPO4-Mediated CKD of Crystallo-Tubular-Nephropathy [CKD-CTN]—A Crystal and Nanotube-Induced Geo-Environmental Disease - Wimalawansa, Sunil J.; Dissanayake, Chandra B. (Frontiers in Water, 2022)
Importance: More than forty million people from certain tropical countries are at risk of developing a non-conventional form of chronic kidney disease (CKD), CKD of multifactorial aetiology (CKDmfo). This is also known as CKD of unknown aetiology (CKDu). Worldwide, it kills more than 20,000 people annually. Findings: CKDmfo is a chronic tubulointerstitial renal disease caused by groundwater-induced hydroxy- and fluorapatite nano-crystals and nano-tube formation in renal tubules and cortical tissues, in conjunction with chronic intravascular volume depletion, chronic renal anaemia, and ischemia. To manifest this gradually developing renal failure, consuming hard water having calcium, phosphates, and fluoride for more than ten years is necessary. The disease progresses when the kidneys fail to repair, ongoing renal tissue damage in the presence of micronutrient deficiency, chronic dehydration, renal ischemia, chronic inflammation, and oxidative stress. Conclusion: Consumption of stagnant groundwater concentrated with ions, like Ca2+, PO4, and F- due to prolonged annual droughts over many years, in conjunction with lesser water intake and chronic dehydration, creates a conducive internal milieu for CaPO4 crystallisation in renal tissues. This proposed primary aetiology of the crystal-tubular-nephropathy (CTN) provides an insight into a deeper understanding of the use of cost-effective strategies for prevention, early intervention, and eradication of CKDmfo. In addition to the nano-crystal/nano-tube concept, we provide supporting scientific evidence that Mg2+ in water and the diet does not promote the disease; instead, it prevents crystal formation and developing CKDmfo. Relevance: We present novel CaPO4 hydroxyapatite crystal formation concepts in a hyperosmolar fluid in renal tissues that causes CKDmfo. Besides, the protective (e.g., magnesium) and enhancing (e.g., dehydration, drinking stagnant hard water, etc.) mechanisms that cause CKDmfo are explored. A new understanding of causative mechanisms paves a path for cost-effective targeted interventions to prevent and eliminate CKDmfo. These principles apply to all CKDmfo/CKDu-affected countries to protect the renal health of farm labourers and others who regularly engage in physical work in hot and dry environments. Providing affordable potable water, increasing water consumption, and avoiding harmful behaviours are critical measures for eliminating CKDmfo.